Healing Law, Not Hurting: Building a Therapeutic Jurisprudence-Based Criminal Justice System in Indonesia - Erwin Susilo; Karell Mawla Ibnu Kamali (Faculty of Law, Universitas Lampung, 2025)
Therapeutic Jurisprudence (TJ) offers a humane and rehabilitation-oriented paradigm that moves beyond a purely punitive criminal justice model. This study examines the urgency of implementing TJ in Indonesia and proposes a conceptual criminal justice model to support its application. Using a normative juridical method with statutory, comparative, and conceptual approaches, the study finds that TJ can enhance rehabilitation and reduce recidivism by incorporating defendants’ psychological and social conditions into judicial decision-making. The proposed model integrates Social Research Reports as a key basis for sentencing and strengthens the role of community probation officers in the rehabilitation process. Its implementation requires legal reform, particularly amendments to the Criminal Procedure Code to authorize judges to order Social Research Reports for adult defendants and to reinforce probation institutions. This study contributes to the development of a more inclusive, just, and rehabilitative criminal justice system in Indonesia.